Physicochemical properties and oxidative stability of milk fortified with spray-dried whey protein concentrate–iron complex and in vitro bioaccessibility of the added iron - Banjare, Indrajeet Singh (Array, 2019)
In the present study, spray-dried whey protein concentrate–iron (WPC–Fe) complex was prepared using a laboratory-scale spray drier under the optimized conditions of inlet temperature 180 °C, flow rate 2.66 mL/min and total solids 15 % with the objective to make iron compatible with food products. In order to remove the free iron from the bound iron, standardised method involving centrifugation and ultrafiltration was employed. Further, the retentate was subjected to spray drying to produce WPC–Fe complex. Milk fortified with WPC–Fe complex (γ(iron)=15 mg/L) showed non-significant difference in heat stability, rennet coagulation time, colour estimation, curd tension, viscosity and sensory attributes as compared to control milk.